Explorando o efeito de telas e doses de adubação no crescimento de mudas de Baru - Zanqueta, Thaina Aparecida Soares. [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
The Cerrado has aroused great interest in the use of its soil for agricultural production, destined for livestock production, a fact that puts the survival of several native species at risk. Therefore, its conservation becomes a priority, requiring maintenance and conservation, with the adoption of practices for restoration and revitalization. Among the native species with potential for reforestation is the baru (Dipteryx alata Vog.), whose traditional consumption is basically its nut, composed of bioactives with high antioxidant and anti-inflammatory activity. However, to use this species in the reforestation of degraded areas, there is a need for robust seedlings, with ideal quality standards and that favor growth in the field. To this end, the objective of this research is to evaluate the impact of combinations of screen types and fertilizer doses on the growth and development of seedlings, aiming to improve production techniques and increase the quality of seedlings for use in the recovery of degraded areas, reforestation.The experiment was carried out in a completely randomized experimental design in a 4 x 4 factorial scheme (shading screens X dose of slow-release fertilizer) with 15 replicates. Baru seeds collected from the germplasm bank of the Teaching, Research and Extension Farm – FEPE were used. The seeds were scarified with sandpaper #120, in the region opposite the micropyle and sown at a depth of 1 cm in plastic trays with 15 cells, filled with commercial organic compost. Before sowing, slow-release fertilizer (15-09-12) was incorporated into the substrate in amounts of 0, 2, 4 and 6 g L-1 of substrate. The seedlings were produced in full sun and in agricultural nurseries with 35% shading screens of the thermo-reflective type, black monofilament and red photoconverter. The evaluation was carried out 50 days after sowing, where the following were evaluated: number of leaves; stem diameter; length of aerial part and root system; dry matter of aerial part and root system.From the results, it was observed that there was a statistical influence in the interaction between the evaluated factors and that the seedlings in full sun presented better results when compared to the others. It was also noted that excessive fertilization can harm the growth of baru seedlings, as in the case of the stem diameter variable in the thermo-reflective screen treatment. It is concluded that the nursery in full sun and an average fertilization of 1.79 g L⁻¹ presented the best result, demonstrating a balance between the fertilization doses and the growth of the seedlings.

The Cerrado has aroused great interest in the use of its soil for agricultural production, destined for livestock production, a fact that puts the survival of several native species at risk. Therefore, its conservation becomes a priority, requiring maintenance and conservation, with the adoption of practices for restoration and revitalization. Among the native species with potential for reforestation is the baru (Dipteryx alata Vog.), whose traditional consumption is basically its nut, composed of bioactives with high antioxidant and anti-inflammatory activity. However, to use this species in the reforestation of degraded areas, there is a need for robust seedlings, with ideal quality standards and that favor growth in the field. To this end, the objective of this research is to evaluate the impact of combinations of screen types and fertilizer doses on the growth and development of seedlings, aiming to improve production techniques and increase the quality of seedlings for use in the recovery of degraded areas, reforestation.The experiment was carried out in a completely randomized experimental design in a 4 x 4 factorial scheme (shading screens X dose of slow-release fertilizer) with 15 replicates. Baru seeds collected from the germplasm bank of the Teaching, Research and Extension Farm – FEPE were used. The seeds were scarified with sandpaper #120, in the region opposite the micropyle and sown at a depth of 1 cm in plastic trays with 15 cells, filled with commercial organic compost. Before sowing, slow-release fertilizer (15-09-12) was incorporated into the substrate in amounts of 0, 2, 4 and 6 g L-1 of substrate. The seedlings were produced in full sun and in agricultural nurseries with 35% shading screens of the thermo-reflective type, black monofilament and red photoconverter. The evaluation was carried out 50 days after sowing, where the following were evaluated: number of leaves; stem diameter; length of aerial part and root system; dry matter of aerial part and root system.From the results, it was observed that there was a statistical influence in the interaction between the evaluated factors and that the seedlings in full sun presented better results when compared to the others. It was also noted that excessive fertilization can harm the growth of baru seedlings, as in the case of the stem diameter variable in the thermo-reflective screen treatment. It is concluded that the nursery in full sun and an average fertilization of 1.79 g L⁻¹ presented the best result, demonstrating a balance between the fertilization doses and the growth of the seedlings.
Exploring the effect of screens and fertilizer doses on the growth of Baru seedlings
Keywords: Dipteryx alata Vog; Telados; Reflorestamento; Cerrado